A method for preparing anode catalyst of proton exchange membrane fuel cell
The proton exchange membrane fuel cell anode catalyst is prepared by step-by-step method, which solves the problems of high iridium consumption and complex pulping process in the prior art, and achieves low-cost and high-performance catalyst preparation.
Patent Information
- Application Number
- CN202411745598.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-02
AI Technical Summary
The amount of iridium is used in existing fuel cell anode catalysts, and the pulping process is complicated, resulting in high costs.
The proton exchange membrane fuel cell anode catalyst is prepared by step-by-step method, and the multi-metal particle size is controlled and the amount of precious metals is used is reduced.
It is achieved that the amount of precious metals is significantly reduced without reducing the anti-reverse ability, simplifying the pulping process and reducing costs.
Smart Images

Figure CN119252952B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fuel cells, and in particular relates to a method for preparing an anode catalyst of a proton exchange membrane fuel cell. Background Art
[0002] A fuel cell is an electrochemical cell comprising two electrodes separated by an electrolyte. A fuel (such as hydrogen or alcohol) is supplied to the anode, and an oxidant (such as oxygen or air) is supplied to the cathode. The electrochemical reaction occurs at the electrodes, and the chemical energy of the fuel and the oxidant is converted into electrical energy and heat. Electrocatalysts are used to promote the electrochemical oxidation of the fuel cell at the anode and the electrochemical reduction of oxygen at the cathode. Since most stack manufacturers have high requirements for the anti-reverse polarity of the membrane electrode, the anti-reverse polarity of the membrane electrode can be enhanced by adding the anti-reverse polarity catalyst iridium oxide to the anode. However, higher anti-reverse polarity often requires a larger amount of iridium catalysts, which will greatly increase the cost of the membrane electrode and the stack. Therefore, the task of developing high-performance, low-precious metal catalysts is very urgent.
[0003] In the prior art, membrane electrodes are generally prepared by adding iridium oxide to the anode. However, this method uses a large amount of iridium and the iridium oxide is easy to precipitate during the pulping process, which increases the difficulty of the membrane electrode pulping process and the cost of the membrane electrode. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a proton exchange membrane fuel cell anode catalyst. The method for preparing a proton exchange membrane fuel cell anode catalyst of the present invention improves the anti-reverse polarity capability while reducing the amount of precious metals used, and is a relatively simple method for achieving low cost of fuel cells.
[0005] In order to achieve the above technical objectives, the technical solution adopted by the embodiment of the present invention is:
[0006] A method for preparing an anode catalyst for a proton exchange membrane fuel cell comprises the following steps:
[0007] (1) Preparation of iridium carbon: carbon powder is added to deionized water, and after being evenly dispersed, an iridium precursor solution, a first reducing agent and an additive are added in sequence, and the pH value of the slurry is adjusted to 3-7 using a first pH adjuster. After heating at 30-100° C. for 10-60 min, solid-liquid separation and drying are performed to obtain iridium carbon;
[0008] (2) Preparation of platinum-iridium carbon: Add deionized water to the iridium carbon obtained in step (1), add the second reducing agent after uniform dispersion, and adjust the slurry particle size to D 90<30μm, add platinum precursor, and use the second pH adjuster to adjust the pH value of the slurry to 7-12, heat at 80-150℃ for 5-60min, and obtain platinum-iridium-carbon catalyst powder through solid-liquid separation, impurity removal and drying.
[0009] Furthermore, the additive in step (1) is selected from one or more of citric acid, sodium citrate, aminotriacetic acid, ethylenediaminetetraacetic acid, ascorbic acid, gluconic acid, 2,3-dihydroxysuccinic acid and oleic acid;
[0010] The additive is added in an amount of 1-50% by mass relative to the carbon powder.
[0011] Furthermore, in step (1), the first pH adjuster is selected from one or more alkaline substances including sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide and ammonia monohydrate to adjust the pH value of the slurry to 5-7.
[0012] Furthermore, the iridium precursor in step (1) is one or more of chloroiridic acid, potassium chloroiridate, iridium chloride and dinitrosodiammineiridium;
[0013] The first reducing agent is selected from at least one of formaldehyde, sodium formate, sodium borohydride, potassium borohydride, ascorbic acid and glucose; and the addition ratio of the first reducing agent to the carbon powder is 10-50% by mass.
[0014] Furthermore, the platinum precursor in step (2) is selected from one or more of chloroplatinic acid, potassium chloroplatinate, platinum chloride and dinitrosodiammineplatinum.
[0015] Furthermore, in step (2), the second reducing agent is selected from at least one of formaldehyde, sodium formate, sodium borohydride, potassium borohydride, ethylene glycol, ascorbic acid and glucose; and the addition ratio of the second reducing agent to the carbon powder is 10-50% by mass.
[0016] The second pH adjuster is selected from one or more alkaline substances including sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide and monohydrated ammonia to adjust the pH value of the slurry to 8-10.
[0017] Furthermore, in step (1), the mass content of iridium in the iridium carbon is 1-50%;
[0018] In step (2), the mass content of platinum in the platinum-iridium-carbon catalyst powder is 20-70%.
[0019] Furthermore, the carbon powder in step (1) is a carbon material, oxide or carbide, and the specific surface area of the carbon powder is 75-2000m 2 / g.
[0020] Furthermore, the carbon powder in step (1) is one or more of carbon black, Ketjen black, mesoporous carbon material, graphitized carbon powder, nanographite and carbon nanotube.
[0021] The technical solution provided by the embodiment of the present invention has the following beneficial effects:
[0022] 1. The method for preparing the anode catalyst of the proton exchange membrane fuel cell of the present invention is a low-temperature reaction, uses simple raw materials, has simple preparation steps and process equipment, and is easy to realize industrial production.
[0023] 2. The preparation method of the anode catalyst of the proton exchange membrane fuel cell of the present invention adopts a step-by-step preparation process, which can realize the control of multi-metal particle size.
[0024] 3. The anode catalyst of the proton exchange membrane fuel cell prepared by the present invention is not easy to settle in the membrane electrode pulping process, which greatly reduces the difficulty of the membrane electrode pulping process.
[0025] 4. Compared with commercial catalysts of the same type, the proton exchange membrane fuel cell catalyst of the present invention can achieve lower performance attenuation before and after polarity reversal with lower precious metal dosage. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a process flow chart of the catalyst preparation process of the present invention.
[0027] Figure 2 This is a comparison of polarization curve performance before and after the membrane electrode anti-reverse polarity test in Example 1 of the present invention.
[0028] Figure 3 This is a comparison of polarization curve performance before and after the membrane electrode anti-reverse polarity test in Example 2 of the present invention.
[0029] Figure 4 This is a comparison of polarization curve performance before and after the membrane electrode anti-reverse polarity test in Example 3 of the present invention.
[0030] Figure 5 This is a comparison of polarization curve performance before and after the membrane electrode anti-reverse polarity test in Example 4 of the present invention.
[0031] Figure 6 This is a comparison of polarization curve performance before and after the membrane electrode anti-reverse polarity test in Example 5 of the present invention.
[0032] Figure 7 This is a comparison of the polarization curve performance of the membrane electrode before and after the anti-reverse polarity test of Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] Example 1
[0035] like Figure 1 As shown, a method for preparing an anode catalyst of a proton exchange membrane fuel cell comprises the following steps:
[0036] (1) Weigh 5 g of XC72 carbon powder, add 200 mL of deionized water, disperse evenly, then add 7.1 g of chloroiridic acid solution (iridium content > 35%), 1.5 g of sodium borohydride and 1 g of ascorbic acid in sequence, adjust the pH value of the slurry to 6.5 by adding sodium hydroxide, heat the slurry at 60° C. for 20 min, perform solid-liquid separation and dry to obtain iridium carbon;
[0037] (2) Add 210 mL of deionized water to the iridium carbon obtained in step (1), add 420 mL of ethylene glycol after it is evenly dispersed, and test the particle size D in the mixed solution using a nanoparticle size analyzer. 90 After the particle size is less than 10 μm, 13.2 g of solid chloroplatinic acid is added, and the pH value of the mixed solution is adjusted to 9 with sodium carbonate. The mixed solution is heated at 120° C. for 15 min, and the platinum-iridium-carbon catalyst is obtained by solid-liquid separation, impurity removal, and drying.
[0038] Preparation method of membrane electrode: accurately weigh 100 mg of the anode catalyst platinum iridium carbon catalyst prepared above; measure 5 mL of pure water, 5 mL of isopropanol and 1 mL of perfluorosulfonic acid resin solution, add them to the catalyst, crush the cells for 40 minutes, form catalyst ink, and evenly coat the ink on the cut proton exchange membrane. When the specific precious metal loading (specific precious metal loading is shown in Table 1) is reached, stop coating and record it as the anode; weigh the cathode catalyst in the same way and coat it on the other side of the above membrane, record it as the cathode, and form a membrane electrode; the gas diffusion layer uses SGL 28BC model GDL. Disassemble the balticFuelCells QCF25 quick assembly test fixture, put in the thickness limit sheet, the first GDL, CCM, and the second GDL in turn, fix them and rotate the pneumatic button to complete the clamping. After connecting the gas pipeline, perform the air tightness test and pass it before performing the single cell test.
[0039] Example 2
[0040] like Figure 1 As shown, a method for preparing an anode catalyst of a proton exchange membrane fuel cell comprises the following steps:
[0041] (1) Weigh 5 g of XC72 carbon powder, add 200 mL of deionized water, disperse evenly, then add 2.9 g of chloroiridic acid solution (iridium content > 35%), 1.5 g of sodium borohydride and 1 g of ascorbic acid in sequence, adjust the pH value of the slurry to 6.5 by adding sodium hydroxide, heat the slurry at 60 ° C for 20 min, separate the solid and liquid, and dry to obtain iridium carbon;
[0042] (2) Add 210 mL of deionized water to the iridium carbon obtained in step (1), add 420 mL of ethylene glycol after it is evenly dispersed, and test the particle size D in the mixed solution using a nanoparticle size analyzer. 90 After the particle size is less than 10 μm, 10.8 g of chloroplatinic acid solid is added, and the pH value of the mixed solution is adjusted to 9 with sodium carbonate. The mixed solution is heated at 120° C. for 15 min, and the platinum-iridium-carbon catalyst is obtained by solid-liquid separation, impurity removal, and drying.
[0043] Preparation method of membrane electrode: accurately weigh 100 mg of the anode catalyst platinum iridium carbon catalyst prepared above; measure 5 mL of pure water, 5 mL of isopropanol and 1 mL of perfluorosulfonic acid resin solution, add them to the catalyst, crush the cells for 40 minutes, form catalyst ink, and evenly coat the ink on the cut proton exchange membrane. When the specific precious metal loading (specific precious metal loading is shown in Table 1) is reached, stop coating and record it as the anode; weigh the cathode catalyst in the same way and coat it on the other side of the above membrane, record it as the cathode, and form a membrane electrode; the gas diffusion layer uses SGL 28BC model GDL. Disassemble the balticFuelCells QCF25 quick assembly test fixture, put in the thickness limit sheet, the first GDL, CCM, and the second GDL in turn, fix them and rotate the pneumatic button to complete the clamping. After connecting the gas pipeline, perform the air tightness test and pass it before performing the single cell test.
[0044] Example 3
[0045] like Figure 1 As shown, a method for preparing an anode catalyst of a proton exchange membrane fuel cell comprises the following steps:
[0046] (1) Weigh 5 g of XC72 carbon powder, add 200 mL of deionized water, disperse evenly, then add 1.3 g of chloroiridic acid solution (iridium content > 35%), 1.5 g of sodium borohydride and 1 g of ascorbic acid in sequence, adjust the pH value of the slurry to 6.5 by adding sodium hydroxide, heat the slurry at 60 ° C for 20 min, separate the solid and liquid, and dry to obtain iridium carbon;
[0047] (2) Add 210 mL of deionized water to the iridium carbon obtained in step (1), add 420 mL of ethylene glycol after it is evenly dispersed, and test the particle size D in the mixed solution using a nanoparticle size analyzer. 90After the particle size is less than 10 μm, 9.8 g of chloroplatinic acid solid is added, and the pH value of the mixed solution is adjusted to 9 with sodium carbonate, and the mixed solution is heated at 120° C. for 15 min. The platinum-iridium-carbon catalyst can be obtained by solid-liquid separation, impurity removal, and drying.
[0048] Preparation method of membrane electrode: accurately weigh 100 mg of the anode catalyst platinum iridium carbon catalyst prepared above; measure 5 mL of pure water, 5 mL of isopropanol and 1 mL of perfluorosulfonic acid resin solution, add them to the catalyst, crush the cells for 40 minutes, form catalyst ink, and evenly coat the ink on the cut proton exchange membrane. When the specific precious metal loading (specific precious metal loading is shown in Table 1) is reached, stop coating and record it as the anode; weigh the cathode catalyst in the same way and coat it on the other side of the above membrane, record it as the cathode, and form a membrane electrode; the gas diffusion layer uses SGL 28BC model GDL. Disassemble the balticFuelCells QCF25 quick assembly test fixture, put in the thickness limit sheet, the first GDL, CCM, and the second GDL in turn, fix them and rotate the pneumatic button to complete the clamping. After connecting the gas pipeline, perform the air tightness test and pass it before performing the single cell test.
[0049] Example 4
[0050] like Figure 1 As shown, a method for preparing an anode catalyst of a proton exchange membrane fuel cell comprises the following steps:
[0051] (1) Weigh 5 g of XC72 carbon powder, add 200 mL of deionized water, disperse evenly, then add 4.8 g of chloroiridic acid solution (iridium content > 35%), 1.5 g of sodium borohydride and 1 g of ascorbic acid in sequence, adjust the pH value of the slurry to 6.5 by adding sodium hydroxide, heat the slurry at 60° C. for 20 min, perform solid-liquid separation and dry to obtain iridium carbon;
[0052] (2) Add 210 mL of deionized water to the iridium carbon obtained in step (1), add 420 mL of ethylene glycol after it is evenly dispersed, and test the particle size D in the mixed solution using a nanoparticle size analyzer. 90 After the particle size is less than 10 μm, 4.5 g of solid chloroplatinic acid is added, and the pH value of the mixture is adjusted to 9 with sodium carbonate. The mixture is heated at 120° C. for 15 min, and the platinum-iridium-carbon catalyst is obtained by solid-liquid separation, impurity removal, and drying.
[0053] Preparation method of membrane electrode: accurately weigh 100 mg of the anode catalyst platinum iridium carbon catalyst prepared above; measure 5 mL of pure water, 5 mL of isopropanol and 1 mL of perfluorosulfonic acid resin solution, add them to the catalyst, crush the cells for 40 minutes, form catalyst ink, and evenly coat the ink on the cut proton exchange membrane. When the specific precious metal loading (specific precious metal loading is shown in Table 1) is reached, stop coating and record it as the anode; weigh the cathode catalyst in the same way and coat it on the other side of the above membrane, record it as the cathode, and form a membrane electrode; the gas diffusion layer uses SGL 28BC model GDL. Disassemble the balticFuelCells QCF25 quick assembly test fixture, put in the thickness limit sheet, the first GDL, CCM, and the second GDL in turn, fix them and rotate the pneumatic button to complete the clamping. After connecting the gas pipeline, perform the air tightness test and pass it before performing the single cell test.
[0054] Example 5
[0055] like Figure 1 As shown, a method for preparing an anode catalyst of a proton exchange membrane fuel cell comprises the following steps:
[0056] (1) Weigh 5 g of XC72 carbon powder, add 200 mL of deionized water, disperse evenly, then add 0.95 g of chloroiridic acid solution (iridium content > 35%), 1.5 g of sodium borohydride and 1 g of ascorbic acid in sequence, adjust the pH value of the slurry to 6.5 by adding sodium hydroxide, heat the slurry at 60 ° C for 20 min, separate the solid and liquid, and dry to obtain iridium carbon;
[0057] (2) Add 210 mL of deionized water to the iridium carbon obtained in step (1), add 420 mL of ethylene glycol after it is evenly dispersed, and test the particle size D in the mixed solution using a nanoparticle size analyzer. 90 After the particle size is less than 10 μm, 3.6 g of solid chloroplatinic acid is added, and the pH value of the mixed solution is adjusted to 9 with sodium carbonate. The mixed solution is heated at 120° C. for 15 min, and the platinum-iridium-carbon catalyst is obtained by solid-liquid separation, impurity removal, and drying.
[0058] Preparation method of membrane electrode: accurately weigh 100 mg of the anode catalyst platinum iridium carbon catalyst prepared above; measure 5 mL of pure water, 5 mL of isopropanol and 1 mL of perfluorosulfonic acid resin solution, add them to the catalyst, crush the cells for 40 minutes, form catalyst ink, and evenly coat the ink on the cut proton exchange membrane. When the specific precious metal loading (specific precious metal loading is shown in Table 1) is reached, stop coating and record it as the anode; weigh the cathode catalyst in the same way and coat it on the other side of the above membrane, record it as the cathode, and form a membrane electrode; the gas diffusion layer uses SGL 28BC model GDL. Disassemble the balticFuelCells QCF25 quick assembly test fixture, put in the thickness limit sheet, the first GDL, CCM, and the second GDL in turn, fix them and rotate the pneumatic button to complete the clamping. After connecting the gas pipeline, perform the air tightness test and pass it before performing the single cell test.
[0059] Comparative Example 1
[0060] Accurately weigh commercial anode catalyst 50% platinum carbon and commercial iridium oxide; measure 5mL of pure water, 5mL of isopropanol and 1mL of perfluorosulfonic acid resin solution, add them to the catalyst, crush the cells for 40min, form catalyst ink, and evenly coat the ink on the cut proton exchange membrane. Stop coating when the specific precious metal loading (specific precious metal loading is shown in Table 1), which is recorded as the anode; weigh the cathode catalyst in the same way, coat it on the other side of the above membrane, which is recorded as the cathode, to form a membrane electrode; the gas diffusion layer uses SGL 28BC model GDL. Disassemble the balticFuelCells QCF25 quick assembly test fixture, put in the thickness limit sheet, the first GDL, CCM, and the second GDL in turn, fix them and rotate the pneumatic button to complete the clamping. After connecting the gas pipeline, perform the air tightness test and pass it before performing the single cell test.
[0061] Single cell test conditions in Examples 1-5 and Comparative Example 1: Single cell area 25 cm 2 , the stoichiometric ratio of anode to cathode is 1.5:2.5, the anode dew point is set to 64°C, the cathode dew point is 64°C, the anode inlet pressure is 1.6 bar, the cathode inlet pressure is 1.5 bar, and the battery test temperature is 80°C.
[0062] The precious metal loading on the membrane electrode prepared by using the catalysts of Examples 1-5 and Comparative Example 1 and the potential decay results before and after the single cell anti-reverse pole test are shown in Table 1. As can be seen from Table 1, compared with the anti-reverse pole test data of the membrane electrode prepared by the commercial anode catalyst, the membrane electrodes of Examples 2 and 3 achieve no potential decay before and after the reverse pole for 120 minutes, which shows that the catalyst prepared by the preparation method of the present invention has better anti-reverse pole performance, and the amount of precious metal used is lower than that of the commercial membrane electrode.
[0063] Table 1 Precious metal loading on membrane electrode in Examples 1-5 and Comparative Example 1, potential decay before and after anti-reverse polarity test
[0064]
[0065] Figure 2-7 It is a comparison of the polarization curve performance of the membrane electrode before and after the reverse pole test in Examples 1-5 and Comparative Example 1 of the invention. It can be seen that the potential of the membrane electrode in Examples 2 and 3 has no decay before and after 120 minutes of reverse pole.
[0066] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A method for preparing an anode catalyst for a proton exchange membrane fuel cell, characterized in that: The following steps are involved: (1) Preparation of iridium carbon: carbon powder is added to deionized water, and after being evenly dispersed, an iridium precursor solution, a first reducing agent and an additive are added in sequence, and the pH value of the slurry is adjusted to 3-7 using a first pH adjuster. After heating at 30-100° C. for 10-60 min, solid-liquid separation and drying are performed to obtain iridium carbon, wherein the mass content of iridium in the iridium carbon is 1-50%; The additive is added at a ratio of 1-50% to the carbon powder, and the first reducing agent is added at a ratio of 10-50% to the carbon powder by mass; (2) Preparation of platinum-iridium carbon: Add deionized water to the iridium carbon obtained in step (1), add the second reducing agent after uniform dispersion, and adjust the slurry particle size to D 90 <30μm, add a platinum precursor, and use a second pH regulator to adjust the pH value of the slurry to 7-12, heat at 80-150°C for 5-60min, and obtain a platinum-iridium-carbon catalyst powder by solid-liquid separation, impurity removal, and drying, wherein the mass content of platinum in the platinum-iridium-carbon catalyst powder is 20-70%; The added ratio of the second reducing agent to the carbon powder is 10-50% by mass.
2. The method for preparing a proton exchange membrane fuel cell anode catalyst according to claim 1, characterized in that: The additive in step (1) is selected from one or more of citric acid, sodium citrate, aminotriacetic acid, ethylenediaminetetraacetic acid, ascorbic acid, gluconic acid, 2,3-dihydroxysuccinic acid and oleic acid.
3. The method for preparing a proton exchange membrane fuel cell anode catalyst according to claim 1, characterized in that: In step (1), the first pH adjuster is selected from one or more alkaline substances including sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide and ammonia monohydrate to adjust the pH value of the slurry to 5-7.
4. The method for preparing a proton exchange membrane fuel cell anode catalyst according to claim 1, characterized in that: The iridium precursor in step (1) is one or more of chloroiridic acid, potassium chloroiridate, iridium chloride and dinitrosodiamineiridium; The first reducing agent is selected from at least one of formaldehyde, sodium formate, sodium borohydride, potassium borohydride, ascorbic acid and glucose.
5. The method for preparing a proton exchange membrane fuel cell anode catalyst according to claim 1, characterized in that: The platinum precursor in step (2) is selected from one or more of chloroplatinic acid, potassium chloroplatinate, platinum chloride and dinitrosodiammineplatinum.
6. The method for preparing a proton exchange membrane fuel cell anode catalyst according to claim 1, characterized in that: In step (2), the second reducing agent is selected from at least one of formaldehyde, sodium formate, sodium borohydride, potassium borohydride, ethylene glycol, ascorbic acid and glucose; The second pH adjuster is selected from one or more alkaline substances including sodium hydroxide, sodium carbonate, sodium bicarbonate, potassium hydroxide and ammonia monohydrate, and the pH value of the slurry is adjusted to 8-10.
7. The method for preparing anode catalyst of proton exchange membrane fuel cell according to claim 1, characterized in that: The carbon powder in step (1) is a carbon material, an oxide or a carbide, and the specific surface area of the carbon powder is 75-2000m 2 / g.
8. The method for preparing a proton exchange membrane fuel cell anode catalyst according to claim 1, characterized in that: The carbon powder in step (1) is one or more of carbon black, mesoporous carbon material, graphitized carbon powder, nanographite and carbon nanotube.
Citation Information
Patent Citations
Preparation method of catalyst with core-shell structure for low-temperature fuel cell
CN102500365A
High-performance Pt-based three-alloy catalyst and preparation method thereof
CN110635146A